Committee on Human Rights: Year in Review 2020 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2020, including information on its advocacy, events, and awareness-raising projects.

Committee on Human Rights: Year in Review 2021 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2021, including information on its advocacy, events, and awareness-raising projects.

Review of the SBIR and STTR Programs at the National Science Foundation - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The National Science Foundation (NSF) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of the NSF Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Drawing on published research plus existing data, Review of the SBIR and STTR Programs at the National Science Foundation analyzes the effectiveness of NSF award selection process and postaward assistance; the effectiveness of the STTR program in stimulating new collaborations; the economic and noneconomic impacts of the programs; effectiveness of the programs in stimulating technological innovation and supporting small, new firms across the technological spectrum; and the role of the programs in providing early capital to firms without other significant sources of support.

Committee on Human Rights: Year in Review 2019 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2019, including information on its advocacy, events, and awareness-raising projects.

For Attribution: Developing Data Attribution and Citation Practices and Standards: Summary of an International Workshop - National Research Council (The National Academies Press, 2012)
The growth of electronic publishing of literature has created new challenges, such as the need for mechanisms for citing online references in ways that can assure discoverability and retrieval for many years into the future. The growth in online datasets presents related, yet more complex challenges. It depends upon the ability to reliably identify, locate, access, interpret, and verify the version, integrity, and provenance of digital datasets. Data citation standards and good practices can form the basis for increased incentives, recognition, and rewards for scientific data activities that in many cases are currently lacking in many fields of research. The rapidly-expanding universe of online digital data holds the promise of allowing peer-examination and review of conclusions or analysis based on experimental or observational data, the integration of data into new forms of scholarly publishing, and the ability for subsequent users to make new and unforeseen uses and analyses of the same data-either in isolation, or in combination with, other datasets. The problem of citing online data is complicated by the lack of established practices for referring to portions or subsets of data. There are a number of initiatives in different organizations, countries, and disciplines already underway. An important set of technical and policy approaches have already been launched by the U.S. National Information Standards Organization (NISO) and other standards bodies regarding persistent identifiers and online linking. The workshop summarized in For Attribution – Developing Data Attribution and Citation Practices and Standards: Summary of an International Workshop was organized by a steering committee under the National Research Council's (NRC's) Board on Research Data and Information, in collaboration with an international CODATA-ICSTI Task Group on Data Citation Standards and Practices. The purpose of the symposium was to examine a number of key issues related to data identification, attribution, citation, and linking to help coordinate activities in this area internationally, and to promote common practices and standards in the scientific community.

Discussion of the Committee on Daubert Standards: Summary of Meetings - National Research Council (The National Academies Press, 2006)

Review of Research Proposals for Cooperation with Former Soviet Biological Weapons Personnel and Institutes: Letter Report from 2000-2004 Reviews - National Research Council (The National Academies Press, 2005)
An ongoing committee of the National Research Council assists the Department of Defense in the development and implementation of a program of expanded scientific cooperation and exchange in peaceful applications of the biological sciences between American research scientists and Russian research scientists who had participated in the biological weapons program of the former Soviet Union. The committee reviews project proposals submitted to DOD by research scientists from Russia, suggests potential collaborators from the United States, and evaluates results of collaborative projects. This report lists the proposals considered from 2000-2004 and summarizes the committee's recommendations.

Committee on Human Rights: Year in Review 2017 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2017, including information on its advocacy, events, and awareness-raising projects.

Committee on Human Rights: Year in Review 2018 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2018, including information on its advocacy, events, and awareness-raising projects.

Monitoring International Labor Standards: Quality of Information: Summary of a Workshop - National Research Council (The National Academies Press, 2003)
The NRC has convened the Committee on Monitoring International Labor Standards to provide expert, science-based advice on monitoring compliance with international labor standards. The committee held a workshop in July 2002 to assess the quality of information and measures of progress towards compliance with international labor standards.This document summarizes the workshop. Reflecting the workshop agenda, this report focuses primarily on the availability and quality of information to measure compliance with four core international labor standards that were identified in 1998 by the ILO. The goal of this workshop summary is to communicate the key ideas and themes that emerged from the workshop presentations and discussions.

Monitoring International Labor Standards: Techniques and Sources of Information - National Research Council (The National Academies Press, 2004)
This new report provides a framework within which to assess compliance with core international labor standards and succeeds in taking an enormous step toward interpreting all relevant information into one central database. At the request of the Bureau of International Labor Affairs at the U.S. Department of Labor, the National Research Council2019s Committee on Monitoring International Labor Standards was charged with identifying relevant and useful sources of country-level data, assessing the quality of such data, identifying innovative measures to monitor compliance, exploring the relationship between labor standards and human capital, and making recommendations on reporting procedures to monitor compliance. The result of the committee2019s work is in two parts2014this report and a database structure. Together, they offer a first step toward the goal of providing an empirical foundation to monitor compliance with core labor standards. The report provides a comprehensive review of extant data sources, with emphasis on their relevance to defined labor standards, their utility to decision makers in charge of assessing or monitoring compliance, and the cautions necessary to understand and use the quantitative information.

Monitoring International Labor Standards: Summary of Domestic Forums - National Research Council (The National Academies Press, 2003)
Over the past half century, the international flow of goods, services, and capital has grown rapidly. Globalization creates new economic, cultural, and social opportunities, but also poses the challenge of ensuring that workers throughout the world share in these opportunities. Responding to this challenge, the U.S. government carries out a variety of policies and programs aimed at encouraging greater recognition of worker rights around the globe. The U.S. Department of State monitors worker rights abroad and reports on the status of those rights as part of its annual report to Congress in the Country Reports on Human Rights Practices. Building on this history of monitoring and encouraging worker rights around the world, the Trade Act of 2002 includes on the list of overall trade negotiating objectives of the United States, promote respect for worker rights. Monitoring International Labor Standards provides expert, science-based advice on monitoring compliance with international labor standards. This report identifies relevant, valid, reliable, and useful sources of country-level data on labor standards; assesses the quality of existing and potential data and indicators that can be used to systematically monitor labor practices and the effectiveness of enforcement in order to determine compliance with national labor legislation and international standards; identifies innovative measures to determine compliance with international labor standards on a country-by-country basis and to measure progress on improved labor legislation and enforcement; explores the relationship between labor standards compliance and national policies relating to human capital issues; and recommends sustainable reporting procedures to monitor countries' progress toward implementation of international labor standards.

Review of the Scientific Approaches Used During the FBI's Investigation of the 2001 Anthrax Letters - National Research Council (The National Academies Press, 2011)
Less than a month after the September 11, 2001 attacks, letters containing spores of anthrax bacteria (Bacillus anthracis, or B. anthracis) were sent through the U.S. mail. Between October 4 and November 20, 2001, 22 individuals developed anthrax; 5 of the cases were fatal. During its investigation of the anthrax mailings, the FBI worked with other federal agencies to coordinate and conduct scientific analyses of the anthrax letter spore powders, environmental samples, clinical samples, and samples collected from laboratories that might have been the source of the letter-associated spores. The agency relied on external experts, including some who had developed tests to differentiate among strains of B. anthracis. In 2008, seven years into the investigation, the FBI asked the National Research Council (NRC) of the National Academy of Sciences (NAS) to conduct an independent review of the scientific approaches used during the investigation of the 2001 B. anthracis mailings. Review of the Scientific Approaches Used During the FBI's Investigation of the Anthrax Letters evaluates the scientific foundation for the techniques used by the FBI to determine whether these techniques met appropriate standards for scientific reliability and for use in forensic validation, and whether the FBI reached appropriate scientific conclusions from its use of these techniques. This report reviews and assesses scientific evidence considered in connection with the 2001 Bacillus anthracis mailings.

Section 230 Protections: Can Legal Revisions or Novel Technologies Limit Online Misinformation and Abuse?: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine
Congress enacted Section 230 to foster the growth of the internet by providing certain immunities for internetbased technology companies. Section 230 contains two key immunity provisions. The first specifies that a provider of an interactive computer service shall not \

A Review of the New Initiatives at the NASA Ames Research Center: Summary of a Workshop - National Research Council (The National Academies Press, 2001)
NASA Ames Research Center, in the heart of Silicon Valley, is embarking on a program to develop a science and technology park bringing together leading companies and universities to capitalize on Ames2019 exceptional mission and location. Other initiatives under consideration include the integration of SBIR grants with a planned on-site incubator, virtual collaboration, and possibly a new public venture capital program. The STEP Board was asked by the NASA Administrator to hold a one-day symposium to review these initiatives. This report includes commissioned research papers and a summary of the proceedings of the symposium organized in response to the NASA request.

Review of Proposals for Research on Statistical Methodologies for Assessing Variables in Eyewitness Performance - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Recognizing the importance of eyewitness identifications in courts of law and motivated by data showing that at least one erroneous eyewitness identification was associated with almost 75% of cases where defendants were later exonerated by DNA evidence, in 2013 the Laura and John Arnold Foundation asked the National Academy of Sciences to undertake an assessment of the scientific research on eyewitness identification and offer recommendations to improve eyewitness performance. The appointed committee issued its report, Identifying the Culprit: Assessing Eyewitness Identification, in 2014. In order to stimulate new and innovative research on statistical tools and the interrelationships between system and estimator variables, the Arnold Foundation in 2015 again called upon the National Academies. This report describes the development of the request for proposals, the processes followed by the committee as it evaluated the proposals, and the committee2019s assessment of the scientific merit and research design of the proposals.

Review of Research Proposals for Cooperation with Former Soviet Biological Weapons Personnel and Institutes: Letter Report from December 2, 2005 Review - National Research Council (The National Academies Press, 2006)
An ongoing committee of the National Research Council assists the Department of Defense in the development and implementation of a program of expanded scientific cooperation and exchange in peaceful applications of the biological sciences between American research scientists and Russian research scientists who had participated in the biological weapons program of the former Soviet Union. The committee reviews project proposals submitted to DOD by research scientists from Russia, suggests potential collaborators from the United States, and evaluates results of collaborative projects. This letter report provides the committee2019s assessment of the proposals considered at its December 2, 2005, meeting.

Review of Research Proposals for Cooperation with Former Soviet Biological Weapons Personnel and Institutes: Letter Report from June 27, 2005 Review - National Research Council (The National Academies Press, 2005)
An ongoing committee of the National Research Council assists the Department of Defense in the development and implementation of a program of expanded scientific cooperation and exchange in peaceful applications of the biological sciences between American research scientists and Russian research scientists who had participated in the biological weapons program of the former Soviet Union. The committee reviews project proposals submitted to DOD by research scientists from Russia, suggests potential collaborators from the United States, and evaluates results of collaborative projects. This letter report provides the committee2019s assessment of the proposals considered at its June 27, 2005, meeting.

Monitoring International Labor Standards: National Legal Frameworks: Summary of a Workshop - National Research Council (The National Academies Press, 2003)
The National Research Council has convened the Committee on Monitoring International Labor Standards to provide expert, science-based advice on monitoring compliance with international labor standards. The committee has undertaken a two-year project with multiple intersecting activities.The committee is charged with assembling information on country compliance with international labor standards and organizing these data into an easily accessible, web-based format for use by the DOL. As one step in this process, a workshop in November 2002 was held to discuss national legal frameworks and the challenges of measuring the extent to which international standards have been incorporated into national laws and practices. Monitoring International Labor Standards is the summary of that workshop. This report communicates the key ideas and themes that emerged from the workshop presentations and discussions.

Monitoring International Labor Standards: International Perspectives: Summary of Regional Forums - National Research Council (The National Academies Press, 2004)
In February and March 2003, the Committee on Monitoring International Labor Standards (CMILS) of the National Research Council (NRC) convened regional forums in Costa Rica, Sri Lanka, and South Africa. Participants included representatives from the International Labour Organization (ILO), national governments, workers' and employers' organizations, nongovernmental organizations (NGOs), and the academic community. These meetings were designed to provide the CMILS with a broad range of international perspectives on the many complex issues related to monitoring compliance with international labor standards, particularly within developing countries. The CMILS has convened similar forums in the United States and held workshops examining data quality, assessing national legal frameworks, and exploring linkages between human capital development and compliance with labor standards.